TINGKAT PENGETAHUAN SWAMEDIKASI DALAM PENANGANAN DEMAM PADA ANAK OLEH IBU DI RW 5 DUSUN SIDOHARUM SEMPOR KEBUMEN - Rafila, R; Miyarso, Chondro Suro (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
All age levels of humans can experience high heat or fever, it occurs because of various possibilities for the entry of seeds of disease into the body. However, cases of fever in infants and toddlers cannot be ignored. Treatment and handling is much different from adults, if the treatment and handling is wrong, slow and inappropriate will result in disruption of the development and growth of the body in infants and the safety of his soul can also be threatened. Therefore parents must master a complete knowledge of fever in children, so that when their children experience a fever it is not panic that arises but rather the right attitude and immediate action or first aid to prevent worse consequences. This research is an observational research with descriptive method. The purpose of this study was to determine the level of knowledge and factors that encourage fever self-medication by mothers in Hamlet Sidoharum RW 05, Sempor. This study was conducted involving 89 respondents. The results of the study showed that the knowledge of respondents in Sidoharum RW 05 village towards self-medication for fever was in the sufficient category.